EFFECT OF HYDROTHERMAL PRETREATMENT AND SOLID SUBSTRATE FERMENTATION USING TRICHODERMA HARZIANUM ON LIGNOCELLULOSE DEGRADATION AND HUMIC ACID SYNTHESIS FROM CORN COB WASTE (ZEA MAYS L.) - Jaifar Husnayan, Rezan
Corn is one of the food crops that has quite high productivity in Indonesia, up to 57.09 quintals/hectare in 2021. The cobs of corn usually only become waste because they are considered to have no value. Corn cobs have quite high lignocellulose content, which is composed of hemicellulose (35-40%), cellulose (20-30%), and lignin (15-20%). One of the lignocellulose derivative products is humic acid, which can be obtained through thermochemical processes such as hydrothermal treatment and fermentation processes by T. harzianum. This research aims to determine the effect of fermentation time and hydrothermal pretreatment time on the degradation of lignocellulose levels and the formation of humic acid levels. Hydrothermal pretreatment of the samples was carried out using an autoclave at a temperature of 121 ? with varying heating times. Variations in fermentation time are 7, 14, 21, 28, and 35 days, while variations in hydrothermal pretreatment time are 30, 45, and 60 minutes. The initial lignocellulose content of corn cobs decreased while the initial humic acid content increased with increasing length of hydrothermal pretreatment time. After the fermentation process, the lignocellulose content of corn cobs generally decreases and the humic acid content increases as the fermentation time increases. In lignin levels, an increase was found due to the lignification process by the fungus T. harzianum. The largest percentage reduction in lignocellulose content was hemicellulose content, followed by cellulose and lignin. Maximum humic acid levels were obtained in corn cob samples with a pretreatment time variation of 60 minutes after a 35 day fermentation process, namely 9%. Based on Pearson correlation analysis, it was found that the hemicellulose and cellulose degradation processes had a strong and significant correlation with increasing the yield of humic acid.